ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL PADA MATA PELAJARAN PPKN - Satria, Aditya Pringga; Ulum, Bachrul (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2022)
Technology in education is developing very rapidly. The use of technology-based learning media aims to make it easier for teachers to deliver material so that learning is more enjoyable and varied. The use of digital technology as a learning medium means that teachers have balanced knowledge with technological advances.This study aims to analyze how the use of digital technology-based learning media in PPKN subjects at SDN 1 Ngembel, Watulimo District.The subject in this study focuses on the high class, namely grade 4. This study uses descriptive qualitative research using observation, interviews and questionnaires to teachers of SDN 1 Ngembel, Watulimo District. The results of this study illustrate that it is quite optimal to use digital technology-based learning media in the learning process at SDN 1 Ngembel Watulimo District in PPKN subjects. The use of Technology-Based Learning Media in PPKN Learning at SDN 1 Ngembel, Watulimo District shows the use of Learning Video media gets a percentage of 50% usage, Power Point 30%, Google Classroom 10%, Youtube 5%, Social Media 5%. From this data, teachers more often use Learning Video learning media than other media.